The Role Of HKBP Nommensen’s Students In Students Exchange In The Youth Elite Exchange Program (YEEP) At National Quemoy University Taiwan 2022 - Fratiwi Juita Rajagukguk; Sahlan Tampubolon; Yessy Octavianna (Lembaga Layanan Pendidikan Tinggi (LLDIKTI) Wilayah - 1, 2024)
This article aims to determine the role of students through the Youth Elite Exchange Program (YEEP) student exchange program at National Quemoy University in 2022 in Taiwan. The type of approach used is qualitative through descriptive method. This method is used to describe the factual conditions that occur in the field during the program. Data collection was done through holistic observation (factual and literal) and documentation. Data analysis was done qualitatively through data presentation and conclusion drawing. The results of the data analysis showed that the activities and events that the students participated in during the program not only contributed to the enhancement of their experience in academic and non-academic aspects, but also expanded their network of social and professional relationships. Involvement in these activities develops students' new skills, meets people from different backgrounds, and builds useful connections. This research is important in uncovering the benefits of foreign exchange programs, as well as potentially increasing the motivation of other students to participate. This activity is also an attraction for students from certain campuses or other campuses. Thus, the program has a significant impact in preparing students to face challenges in the world of work and social life.